The adoption of business process reengineering in SMEs: a diffusion of innovation approach. (1st January 2001) - Yung, K.L.; Chan, W.Q.
This study explores how business process reengineering methodology is adopted to innovate the product development process for global manufacture, through the case of a small manufacturing enterprise. Diffusion of innovation theories are used to explain the influence of variables at individual, organisational and environmental levels of analysis. The in-depth case study shows the difficulties innovating processes face in catching up with rapid change management within the changing situation of a dynamic company both in the justification of a BPR project and gaining support through the project. The conclusion is that variables at all three levels are important in explaining the adoption of business process reengineering methodology with the environmental level being considered most powerful in its impact. Given these findings, the authors qualify the predictive power of rational models that focus on the individual level of analysis and urge more balanced methodologies that examine the joint impact of the three levels of analysis for process innovation development in SMEs.